KONTAK AWAL UMAT ISLAM DENGAN PUSAT PERADABAN DUNIA - Humaida Hasibuan (Universitas Islam Negeri Sumatera Utara, 2016)
The source of the human intellect is the Creator God Almighty. The Persian and Roman civilization as world civilization melatari the beginning of Islamic civilization. Muslim intellectual development from a historical point of view continued development of keintelektualan past. Along with that, a muslim tailor, adding ideas, thoughts and ideas of their own into the historical development of such intellectual process called naturalization. If ever, Muslims shut down and has no desire to adopt knowledge from outside Islam, then there are probably Muslims achieve the progress of civilization in time that fast. Past contributions gives a fairly significant influence on the progress and the intellectual brilliance of early Muslims.